PENGARUH KUALITAS PELAYANAN PETUGAS KELURAHAN SUKODADI PALEMBANG TERHADAP KEPUASAN MASYARAKAT (STUDI KASUS PEMBUATAN E-KTP) - sahyuni SE.MM; Annisa Nurul.U (Fakultas Ekonomi Universitas Tridinanti Palembang, 2015)
This study discusses the impact of service quality sukodadi palembang village clerk to the satisfaction of the community. where one of the elements to improve public satisfaction.This research was conducted within 3 months, where the study was conducted in Palembang Sukodadi village is located at KM 12 Jln Idris Lukman Simpang village heads palembang.dalam this case the researchers determine the population using a sample of 2,050 inhabitants with 95 people.Calculation shows that the regression coefficient 0.436 for the variable quality of service and also generate value constants of 37.332 coefficient value then the value of the linear regression is Y = 37.332 + 0.436 X of the correlation coefficient r = 0.383 means that the relationship between service quality is quite variable and the direction (positive correlation ) by 38% with community satisfaction coefficient of determination R Ã‚Â² = Amounting to 0,287. The value can be forecasted that the percentage of influence between the variables of service quality has a considerable influence segnifikan together in the same direction towards the satisfaction of the community.Ã‚Â Keywords : service quality, the satisfaction of the community